Prioritization Of The Indicators And Sub-Indicators Of Maqasid Al-Shariah In Measuring Liveability Of Cities - Dali, Norimah; Abdullah, Alias; Islam, Rafikul (Creative Decisions Foundation, 2018)
Opinions were sought from a panel of two groups of Malaysian experts, i.e., the urban planners and the Maqasid al-Shariah scholars with the aim of developing an evaluation model via identifying and ranking the Maqasid indicators and sub-indicators for liveability and quality of life in cities. The measurement takes off with the Dharuriyyat (essentials or necessities) dimension of the Maqasid al-Shariah principles based on Al-Shatibi’s School of maslahah which targets public interests and benefits living in cities. This is supported by Ibn Ashur and contemporarily by Yusuf al-Qaradhawi who emphasise on harmony, justice and global peace. The Analytic Hierarchy Process (AHP) has been used as a main method to prioritise the indicators and sub-indicators. The AHP results indicate that religion, life, intellect, lineage and wealth are in descending order of importance, similar to the priorities of the classic Maqasid al-Shariah doctrine. However, the sub-indicators are ranked in terms of priorities based on the consensus of the urban planners and maqasid practitioners which ultimately form the Islamic liveability measurement for cities.